A PD-L1 Negative Advanced Gastric Cancer Patient With a Long Response to PD-1 Blockade After Failure of Systematic Treatment: A Case Report - Zhang, Fangyuan; Zhang, Jieying; Zhao, Lei; Zhai, Menglan; Zhang, Tao; Yu, Dandan (Frontiers in Immunology, 2021)
Background It was widely accepted that programmed death-ligand 1 (PD-L1) positive, tumor mutational burden-high (TMB-H) or microsatellite instability-high (MSI-H) tumor are prone to have better treatment response to immune checkpoint blockade. The value of immune checkpoint blockade in PD-L1 negative gastric cancer patients has been questioned due to lower objective response rate (ORR). Case Presentation We report an unusual case of a PD-L1 negative, proficient mismatch repair (pMMR)/microsatellite stability (MSS), tumor mutational burden-low (TMB-L) gastric cancer patient who achieved good response to immune checkpoint blockade after failure of systematic treatment. Multiple lymph nodes and bone metastases are the main characteristics of this patient. The patient survived for more than 30 months after diagnosis. Conclusions This case suggested that PD-L1 negative gastric cancer patient may also benefit from immune checkpoint blockade. In gastric cancer, patients with lymph node metastasis may be potential beneficiaries.